Sintesis Senyawa-Senyawa Epoksi dari Asam Lemak Minyak Nyamplung (Calophyllum inophyllum L.) - Murniati, Murniati; Gunawan, Erin Ryantin; Suhendra, Dedy; Asnawati, Dina -; Qurba, Pujana (Jurnal Riset Kimia, 2022)
Epoxidation is a reaction of a carbon double bond with active oxygen, which results in the addition of an oxygen atom, converting the original double bond into a three-membered epoxide (oxirane) ring. Generally, the raw material for making epoxy comes from petroleum. Nyamplung kernel oil is a non-edible oil that can be used as an alternative raw material for making epoxy derivatives. The purpose of this study was to determine the optimum conditions and characterization of epoxy materials. The fatty acids of Nyamplung kernel oil were reacted formic acid and hydrogen peroxide with sulfuric acid as a catalyst. The optimum condition of the following parameters on the study of this process was investigated: the epoxidation time, temperature, and the mole ratio of formic acid and hydrogen peroxide. The results showed that the optimum reaction conditions with the temperature was 65 oC, the mole ratio of formic acid and hydrogen peroxide was 1:6, and the reaction time was 75 minutes. The results of the characterization under optimum conditions showed the oxirane value of 1.69, the iodine number of 9.63 mg iod/100 g, and the epoxy conversion of 67.6 %. The results of FTIR characterization showed absorption at a wavenumber of 820.03 cm-1 which is a specific absorption from the oxirane ring of the epoxy compound.